2021
DOI: 10.3389/fchem.2021.672744
|View full text |Cite
|
Sign up to set email alerts
|

Application of MALDI-TOF MS Profiling Coupled With Functionalized Magnetic Enrichment for Rapid Identification of Pathogens in a Patient With Open Fracture

Abstract: Posttraumatic infections can occur in orthopedic trauma patients, especially in open fractures. Rapid and accurate identification of pathogens in orthopedic trauma is important for clinical diagnosis and antimicrobial treatment. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been successfully used for first-line identification of pathogens grown on culture plates. However, for direct analysis of liquid clinical specimens, pre-purification of the sample is necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Our previous study introduced the synthetic process for Fc-MBL@Fe 3 O 4 and the characterization of Fc-MBL@Fe 3 O 4 ( 24 , 25 ). Transmission electron microscopy (TEM) images of the binding of Fc-MBL@Fe 3 O 4 to S. aureus are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study introduced the synthetic process for Fc-MBL@Fe 3 O 4 and the characterization of Fc-MBL@Fe 3 O 4 ( 24 , 25 ). Transmission electron microscopy (TEM) images of the binding of Fc-MBL@Fe 3 O 4 to S. aureus are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specific aptamers and antibodies conjugated to MNPs can enrich certain bacteria or some microorganisms from suspension ( 21 23 ). Bacteria in liquid media can be enriched by a novel functionalized magnetic nanoparticle (Fc-MBL@Fe 3 O 4 ) and identified by MALDI-TOF MS ( 24 ). These studies indicated that Fc-MBL@Fe 3 O 4 can effectively purify bacteria from clinical samples or liquid culture media.…”
Section: Introductionmentioning
confidence: 99%
“…Ying et al investigated the possibility of using pathogen enrichment Fc-MBL@Fe 3 O 4 with MALDI-TOF MS profiling to identify pathogens in samples cultured in liquid. They concluded that Fc-MBL@Fe 3 O 4 could recognize and trap broad-spectrum microorganisms and could, therefore, be adapted to be combined with the MALDI-TOF MS technique [ 103 ].…”
Section: Bacteria Identificationmentioning
confidence: 99%
“…In recent years, the developed MALDI-TOF commercial platforms include the Bruker (Bruker Daltonics, Germany) Microflex with the Biotyper database, the bioMérieux (Durham, NC) Vitek MS research-use-only system with the SARAMIS SuperSpectra database, the bioMérieux VitekMS in vitro diagnostic system with the Knowledge Base database, and Meihua (Zhuhai, China) M-Discover 100 mass spectrometer with its database ( 10 , 11 ). Among these, MALDI Biotyper and Vitek MS have been approved by the U.S. Food and Drug Administration ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%